PERAN ORANG TUA SEBAGAI PENDIDIK TERHADAP PRESTASI BELAJAR ANAK SEKOLAH DASAR DI KOTA BIMA - Rosuliana, Novi Enis (STIKES Mataram, 2017)
A parent as an educator has an important role in increasing and stimulatingstudents to learn, therefore the learning process taken by students can increase knowledge, skill, and behavior. Those elements can give good impact toward learning achievement of students in their school.The purpose of this research is recognizing relationship between parents as an educatorwith learning achievement of Student Primary School 01 in Bima City.This research using cross sectional approach by collecting37 respondents as total samplingwhich applies Proportional Technics of stratified random sampling. The analysis result which is using Pearson Product Moment gives asignificant value 0,000 < 0,05, so tha Ha is received which means there is relationship between parents as an educator with learning achievement of Student Primary School 01 Bima City. The recommendation of this research is developing role of parent as an educator in order to obtain students learning achievement at school. Keyword : The role of parents as an educator, student learning achievement.